2003
DOI: 10.1359/jbmr.2003.18.10.1912
|View full text |Cite
|
Sign up to set email alerts
|

TRACP as an Osteopontin Phosphatase

Abstract: TRACP is synthesized as a latent proenzyme requiring proteolytic processing to attain maximal phosphatase activity. Excision of an exposed loop domain abolishes the interaction between the loop residue Asp146 and a ligand to the redox-sensitive iron of the active site, most likely Asn91, providing a mechanism for the enzyme repression. Both cathepsin K and L efficiently cleave in the loop domain and activate the latent enzyme, and we propose that cathepsin K acts as a physiological activator of TRACP in osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…One proposal is that the enzyme generates free radicals that help to dissolve collagen fragments released from bone by cathepsin K [Halleen et al, 1999]. Alternative roles include actions as an osteopontin phosphatase [Andersson et al, 2003], in iron transport [Saunders et al, 1985], and as a growth factor [Bazer et al, 1991;Sheu et al, 2003]. Whatever its function, it has long been known that TRAP levels are increased in the serum of individuals who have a high rate of bone resorption [Stepan et al, 1989;Halleen et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…One proposal is that the enzyme generates free radicals that help to dissolve collagen fragments released from bone by cathepsin K [Halleen et al, 1999]. Alternative roles include actions as an osteopontin phosphatase [Andersson et al, 2003], in iron transport [Saunders et al, 1985], and as a growth factor [Bazer et al, 1991;Sheu et al, 2003]. Whatever its function, it has long been known that TRAP levels are increased in the serum of individuals who have a high rate of bone resorption [Stepan et al, 1989;Halleen et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…After extraction, the RNA was treated with 5 units of DNase I (Invitrogen) for 30 min at room temperature. The reverse transcriptase reaction was performed with 5 g of total RNA and 200 units of Superscript TM II reverse transcriptase (Invitrogen) at 42°C, using (dT) [12][13][14][15][16][17][18] as primer (Invitrogen), according to the protocol of the manufacturer. In negative controls, reverse transcriptase was excluded from the reaction mixture.…”
Section: Relative Quantification Of Cathepsin K and L Mrnamentioning
confidence: 99%
“…Different functions have been suggested for TRAP, e.g. as an osteopontin phosphatase (13)(14)(15), generation of reactive oxygen species (16 -19), iron transport (20 -24), and as a growth/differentiation factor for hematopoietic (25) and osteoblastic (26) cells.…”
mentioning
confidence: 99%
“…5,6 In vivo, TRAP 5b has previously been proposed to function as a generator of reactive oxygen species and as a protein phosphatase regulating the bioactivity of osteopontin. [7][8][9] Recently, we showed that TRAP 5a, but not TRAP 5b, induces obesity in mice and is increased in the adipose tissue of obese humans. 10 Furthermore, TRAP 5a, but not TRAP 5b, induces both proliferation and differentiation of mouse and human adipocyte precursors in vitro.…”
Section: Introductionmentioning
confidence: 99%